Type 1 diabetes and combined acute and chronic complications are associated with risk of progression of liver fibrosis: a Mendelian randomization study - Huo, Guangyuan; Gao, Yueqiu (Frontiers in Endocrinology, 2024)
Background There has been controversy and uncertainty regarding the causal relationship between type 1 diabetes, its consequences, liver fibrosis, and cirrhosis. In order to determine the causal relationship, we conducted a Mendelian randomization study (MR). Methods For the first time, we subjected multiple diabetes data to analyze its relationship with the progression of liver fibrosis. Once the instrumental variables had been extracted, we assessed them employing Cochran’s Q multi-analysis, inverse variance weighted, MR-Egger, MR-PRESSO, weighted mode, and weighted median. Results Genetically predicted type 1 diabetes (OR = 1.13, 95% CI: 1.04–1.23, **P = 3.42 × 10−3), type 1 diabetes without complications (OR = 1.12, 95% CI: 1.03–1.23, *P = 1.26 × 10−2), type 1 diabetes with coma (OR = 1.09, 95% CI: 1–1.18, *P = 4.74 × 10−2), type 1 diabetes with ketoacidosis (OR = 1.07, 95% CI: 1.01–1.13, *P = 1.3 × 10−2), type 1 diabetes with neurological complications (OR = 1.18, 95% CI: 1.11–1.26, ***P = 4.05 × 10−7), type 1 diabetes with ophthalmic complications (OR = 1.16, 95% CI: 1.05–1.28, **P = 3.06 × 10−3), type 1 diabetes with renal complications (OR = 1.07, 95% CI: 1–1.13, *P = 3.45 × 10−2), type 1 diabetes with other specified/multiple/unspecified complications (OR = 1.12, 95% CI: 1.02–1.23, *P = 1.41 × 10−2) were all associated with an increased risk of liver fibrosis progression. Conclusions According to our MR investigation, type 1 diabetes and both its acute and chronic implications may increase the likelihood that liver fibrosis could continue to develop. Additionally, type 1 diabetes with neurological and ocular problems is more likely to accelerate the development of liver fibrosis and inflammation, which offers new insights for genetic investigations.